2021
DOI: 10.1002/pra2.475
|View full text |Cite
|
Sign up to set email alerts
|

#StopAsianHate: Archiving and Analyzing Twitter Discourse in the Wake of the 2021 Atlanta Spa Shootings

Abstract: On March 16, 2021, six Asian women were killed in Atlanta, US, possibly out of racist motivations. This tragic event, now known as the 2021 Atlanta Spa Shootings, precipitated a massive increase in the volume of counter-anti-Asian declarations and discussion on social media platforms such as Twitter. In a pilot study to chronicle and profile public opinions, social movements and patterns in the global Twitter discourse we scraped the Twitter API using the query term "StopAsianHate", obtaining more than 5.5 mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Building off Lopez's (2016) study of Asian American media activists, this paper examines how racial justice activism unfolds online. Existing studies on these particular hashtags, coming largely from the field of computer science, focus on finite time periods during the pandemic, from the immediate weeks following the Atlanta-area shootings (Fan, Huizi, and Gilliland 2021;Lee and Jang 2021;Lyu et al 2023) to the weeks following US President Biden's signing of the COVID-19 Hate Crimes Act (Cao et al 2022). Further, researchers have conducted longitudinal examinations of how counter-hate speech, including these hashtags, interacts with anti-Asian hate speech online (He et al 2020;Lin et al 2022).…”
Section: Anti-asian Racism Online Amidst Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Building off Lopez's (2016) study of Asian American media activists, this paper examines how racial justice activism unfolds online. Existing studies on these particular hashtags, coming largely from the field of computer science, focus on finite time periods during the pandemic, from the immediate weeks following the Atlanta-area shootings (Fan, Huizi, and Gilliland 2021;Lee and Jang 2021;Lyu et al 2023) to the weeks following US President Biden's signing of the COVID-19 Hate Crimes Act (Cao et al 2022). Further, researchers have conducted longitudinal examinations of how counter-hate speech, including these hashtags, interacts with anti-Asian hate speech online (He et al 2020;Lin et al 2022).…”
Section: Anti-asian Racism Online Amidst Covid-19mentioning
confidence: 99%
“…Counts for languages are summarized in Table 2. While some previous papers that analyze #StopAsianHate and #StopAAPIHate focus on English tweets only (Cao et al 2022;Fan, Huizi, and Gilliland 2021;Lyu et al 2023), we purposefully include tweets in other languages within our full dataset in order to examine the effects of the hashtags on a global scale. This is particularly relevant due to the language barriers that motivate specific forms of anti-Asian discrimination and racism-further, as the COVID-19 pandemic has revealed, the perception of race often lacks nuance when it comes to anti-Asian racism, with many non-Chinese background being broadly classified as Chinese when encountering blame for the pandemic.…”
Section: Languagementioning
confidence: 99%
“…While some degree of human input into description is likely to remain desirable [22,41], particularly for providing historical and cultural context, the overall descriptive effort could be ameliorated if certain aspects of those collections could be described automatically and if additional information about the collection as a whole that is not readily discernible to the human eye could be identified.…”
Section: Automating and Iterating Archival Description And Enhancing ...mentioning
confidence: 99%
“…Nevertheless, while it is not subject to the same policy rules and evidentiary scrutiny as bureaucratic records, the trustworthiness and transparency of archival administration of social media content may be a matter of public, and sometimes political concern, especially when it is used as a major organ of government communication [7]. Although many archives and libraries preserve social media content [22], there is a pressing need for more research and testing of computational descriptive methods that can not only eliminate some manual descriptive processes, but also surface new knowledge and increase contextualization. As early as 1992, a statistical content analysis demonstrated that a statistical approach could assist in archival description of the content of early social media implementations, and especially in surfacing latent patterns in that content [28].…”
Section: Archiving Social Mediamentioning
confidence: 99%
“…These contributions provide a rich source of data on this sensitive topic and allow researchers to track, capture, and analyze tweeters’ responses and activities [ 13 ]. In particular, digital data mining of tweets has been used to help identify hot topics and blind spots within the field of racial studies, including in AA Studies [ 16 , 17 ]. Considering the aforementioned features, Twitter is the most appropriate platform to understand public disclosure toward the #StopAsianHate movement.…”
Section: Introductionmentioning
confidence: 99%